Homo Ludens 1(2)/2010 Spis treści - Redaktor (Polskie Towarzystwo Badania Gier, 2010)
Homo Ludens pierwszy ludologiczny periodyk naukowy w Polsce i zarazem oficjalne czasopismo Polskiego Towarzystwa Badania Gier. Tytuł pisma nawiązuje do klasycznej już pozycji holenderskiego historyka i antropologa kultury Johana Huizingi „Homo ludens. Zabawa jako źródło kultury” (1938). Czasopismo publikuje artykuły przeglądowe, polemiczne, ogólne i przyczynkowe, wspomnieniowe oraz wybrane recenzje i sprawozdania w języku polskim, angielskim i niemieckim. Pismo ukazuje się z częstotliwością jednego numeru na rok.

(ang.) Homo Ludens is the official journal of the Games Research Association of Poland (Polskie Towarzystwo Badania Gier). The journal carries original articles on various aspects of ludology as broadly perceived games research in the humanities, social and other sciences. It presents a representative survey of empirical and theoretical research conducted in this area in Poland and abroad as well as reflections on issues in the area of game studies. It also publishes selected book reviews in this area. The language of the journal is basically Polish but articles in English and German are also accepted. At least one issue is published each year.
Keywords: Ludoogy; Game studies; Games research; Games Research Association of Poland; Polskie Towarzystwo Badania Gier; Ludologia; Homo Ludens